The Effect of the Discovery Learning Model Assisted E-Module Creativity and Improving Student Learning Outcomes - Malau, Binro Maldon; Nainggolan, Bajoka (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2024)
The discovery learning model is learning model that is student-centered. This research aims to determine the effect of implementing discovery learning assisted by e-modules on creativity and improving student learning outcomes. The sample was selected by purposive sampling experimental student (with DL assisted by e-modules) and 32 control students (conventional learning). The research carried out by administering a pre-test, then a post-test. Data is processed qualitatively and quantitatively statistics. Results obtained: average creativity of experimental class was 80.2 and the control class 72.3 The N-gain value for the experimental class was 0.712 or an increase in learning outcomes of 71.20% (high), while the control class was 0.60 or an increase in learning outcomes of 60.0% (medium). The correlation between creativity and increased learning outcomes obtained at 0.467 with a determination index of 21%. Learning with DL assisted by e-modules has an effect on creativity and improving student chemistry learning outcomes on reaction rate material.